Memorable ecotourism experiences in Taman Negara, Pahang - Subramaniam, Thanam; Samdin, Zaiton; Ramachandran, Sridar; Kunasekaran, Puvaneswaran (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
Memorable Ecotourism Experiences (MEEs) playa key role in obtaining tourists’ satisfaction and loyalty in sustaining the ecotourism destination. Although, MTEs has been recognised as a crucial area of tourism studies since 2010, but still there is a lack of study that explore all dimensions or constructs of MTEs. Most of the recent studies only tested eight significant constructs and ignored the remaining constructs. Therefore, this study aim to examine the dimensions that influences the memorable ecotourism experiences in Taman Negara, Pahang Malaysia. Subsequently, to propose a MEEs model. In order to fill the literature gap, a pilot test was conducted in April 2018 with a sample of 40 tourists to Taman Negara, Pahang, Malaysia. These preliminary results indicated that 15 out of 22 constructs (hedonism, knowledge, meaningfulness, local culture, novelty-familiarity, involvement, refreshing, destination attributes, service, participation, freeing, adverse feeling, socialization, nature and education awareness) were significantly influencing the MEEs in Taman Negara. The study recommends further studies to be conducted to explore all 22 proposed constructs in a variety of ecotourism sector.